A highly selective C-rhamnosyltransferase from Viola tricolor and insights into its mechanisms - Bo-Yun Han; Zi-Long Wang; Junhao Li; Qing Jin; Hao-Tian Wang; Kuan Chen; Yang Yi; Hans Ågren; Xue Qiao; Min Ye (Elsevier, 2023)
C-Glycosides are important natural products with various bioactivities. In plant biosynthetic pathways, the C-glycosylation step is usually catalyzed by C-glycosyltransferases (CGTs), and most of them prefer to accept uridine 5'-diphosphate glucose (UDP-Glc) as sugar donor. No CGTs favoring UDP-rhamnose (UDP-Rha) as sugar donor has been reported, thus far. Herein, we report the first selective C-rhamnosyltransferase VtCGTc from the medicinal plant Viola tricolor. VtCGTc could efficiently catalyze C-rhamnosylation of 2-hydroxynaringenin 3-C-glucoside, and exhibited high selectivity towards UDP-Rha. Mechanisms for the sugar donor selectivity of VtCGTc were investigated by molecular dynamics (MD) simulations and molecular mechanics with generalized Born and surface area solvation (MM/GBSA) binding free energy calculations. Val144 played a vital role in recognizing UDP-Rha, and the V144T mutant could efficiently utilize UDP-Glc. This work provides a new and efficient approach to prepare flavonoid C-rhamnosides such as violanthin and iso-violanthin.